The hybrid nature of social enterprises how does it affect their revenue sources?. Issue 2 (28th October 2021) - Searing, Elizabeth A.M.; Poledrini, Simone; Young, Dennis R.; Nyssens, Marthe
Abstract : Purpose: This paper aims to examine the applicability of the benefits theory of nonprofit finance to an international sample of social enterprises (SEs). Design/methodology/approach: This research analyzes the revenue sources of SEs through the lens of benefits theory. In particular, the authors test the links between revenue sources and the character of an enterprise's mission. This study uses data on 545 SEs collected by the International Comparative Social Enterprise Models project, which was an international collaborative effort of more than 200 researchers. The authors use cross-sectional multivariate regression to identify the factors which influence the revenue portfolios of SEs. Findings: The findings provide evidence of SE revenue portfolios that are nuanced and complicated. Benefits theory helps to illuminate this nuance. The application of benefits theory to SE goes beyond the traditional characterization of the publicness and privateness of goods and services to include the intended beneficiaries, the nature of benefits they receive and the management practices followed to assure distribution of benefits to intended beneficiary groups. By analyzing the public (and private) goals of SEs, such as employment generation and food security, the authors gain an understanding of what they really do, and hence, how they can be best financed. Originality/value: This study provides empirical support to the applicability of benefits theory to SEs, which provides both theoretical advancement and practical implications.